Educação e gestão socioambiental: a experiência do programa Catavida de Novo Hamburgo – RS - Rios, Thais de Miranda (Universidade do Vale do Rio dos Sinos, 2015)
This research aims to contribute to the dialogue and socio-educational practices, understanding the potential and existing relationships between education and socio- environmental management in the context of social administration of recyclable solid waste. From the systemic thought/thinking, which understands life in motion, it was intended to contribute to a complex understanding of relational solidarity, friendly and fair coexistence among all Cosmos beings, unlike the anthropocentric thinking. The empirical field is the experience of socio-environmental program CATAVIDA of Novo Hamburgo - RS, a collectors training program simultaneously with solid waste management in some cities. For the collection and production of information we analized documents on the website, physical documents found/located at the Development Department, and observations of individual and group interviews. Among the key findings, it is emphasized the importance of educators and managers know deeply, in a systemic way, the roots of the environmental problem to develop coherent projects of educational nature that integrate the social and economic dimension, coordinating the management of selective collection and treatment of household waste.
Keywords: Educação socioambiental; Educação e gestão; Cidadania; Sustentabilidade; Environmental education; Management; Education; Citizenship; Sustainability; ACCNPQ::Ciências Humanas::Educação